Variation in fine root biomass along a 1000 km long latitudinal climatic gradient in mixed boreal forests of North-East Europe - Leena Finér; Vitali Zverev; Marjo Palviainen; Tatiana Romanis; Mikhail V. Kozlov (ELSEVIER SCIENCE BV, 2022)
The geographical patterns in the distribution of fine root biomass (FRB) and in the contribution of fine roots to below-ground nitrogen and carbon stocks are poorly documented. Here, we examined FRB and the ecological factors that govern it, along a 1000 km long latitudinal gradient in unmanaged mixed boreal forests in North-East Europe. We sampled fine roots (diameter >= 2 mm; trees and field layer vegetation combined) twice per growing season in 2015 and 2016 from ten sites spaced one degree of latitude between 60 degrees N (near St. Petersburg) and 69 degrees N (near Murmansk, Russia). We separated living fine roots. The roots were dried and weighed; tissue carbon and nitrogen concentrations were measured. The obtained values were correlated with climatic, plant community and soil characteristics. Among-site variation in the total FRB and carbon and nitrogen concentrations were not explained by latitude or by climatic, plant community or soil characteristics. However, fine root density in the organic layer increased towards the north. The more superficial root system in the north than in the south may indicate a poleward increase in the vulnerability of boreal forests to abiotic risks (forest fires, drought). Our results suggest that the future climate may shift fine roots as well as carbon and nitrogen cycling from the organic layer to mineral soils, thereby increasing the volume of soil utilized by fine roots for water and nutrient uptake.